Saving for change, a local financing mechanism that enhances women use to climate smart agriculture innovations - Dossou-Yovo, Elliott Ronald; Koné, Pierre; Akpoffo M., Marius; Guindo, Samuel (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
AICCRA-Mali promoted the 'Savings Clubs,' which enhanced financial accessibility for 35,000 women farmers in Mali. Women beneficiaries have increased their investments in agricultural production and embraced CSA innovations, including farm diversification with vegetables, seeds of drought-resistant varieties, and supplementary irrigation. On average, women beneficiaries increased their investments in CSA innovations by USD 120/ha, resulting in an increase in income by USD 618/ha, a net income by USD 497/ha and food consumption score by 12. When the cumulative benefits of the Saving for Change mechanism over the total cultivated area of the beneficiaries was assessed, the saving for change financing mechanism increased cultivated area by 15,135 ha, investment in agriculture by 4.2 million USD/ha, farmers’ income by 17.4 million USD. Besides, women engaged in Saving for Change group were more food secure than the farmers who were not engaged in the Saving for Change group.